Letermovir prophylaxis for cytomegalovirus is associated with risk of post-transplant lymphoproliferative disorders after haploidentical stem cell transplantation - Xu-Ying Pei; Qiang Huang; Ling-Jie Luo; Hai-Lu Sun; Jing Liu; Yu-Qian Sun; Xiao-Dong Mo; Meng Lv; Dai-Hong Liu; Hong-Yan Ma; Yan-Wei Wu; Lan-Ping Xu; et al. (Haematologica)
Not available.